2012
DOI: 10.1002/mus.23389
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based guideline: Neuromuscular ultrasound for the diagnosis of carpal tunnel syndrome

Abstract: Neuromuscular ultrasound measurement of median nerve cross-sectional area at the wrist is accurate and may be offered as a diagnostic test for CTS (Level A). Neuromuscular ultrasound probably adds value to electrodiagnostic studies when diagnosing CTS and should be considered in screening for structural abnormalities at the wrist in those with CTS (Level B).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
256
2
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(289 citation statements)
references
References 63 publications
9
256
2
13
Order By: Relevance
“…In CTS, the swelling of the nerve at the tunnel inlet has been very early recognized as a consistent sign of compression within the tunnel (Buchberger et al, 1991) and has become the mainstay for the ultrasonographic diagnosis of CTS (Cartwright et al, 2012;Tai et al, 2012). It has been postulated that the swelling resulting from compression is translated to the site of least resistance, which explains why it is seen at the proximal edge of the retinaculum, at the tunnel inlet, where the nerve is relieved from pressure, rather than within the confined space of the tunnel (Therimadasamy et al, 2012;Paliwal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CTS, the swelling of the nerve at the tunnel inlet has been very early recognized as a consistent sign of compression within the tunnel (Buchberger et al, 1991) and has become the mainstay for the ultrasonographic diagnosis of CTS (Cartwright et al, 2012;Tai et al, 2012). It has been postulated that the swelling resulting from compression is translated to the site of least resistance, which explains why it is seen at the proximal edge of the retinaculum, at the tunnel inlet, where the nerve is relieved from pressure, rather than within the confined space of the tunnel (Therimadasamy et al, 2012;Paliwal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analyses of the large body of literature that has accumulated in the past two decades (Cartwright et al, 2012;Tai et al, 2012) showed that level A evidence support the ultrasonographic measurement of median nerve crosssectional area at the tunnel inlet (CSA-I) as an accurate diagnostic test for CTS (Cartwright et al, 2012). The cut-off value of CSA-I showed a wide range of variation between 8 and 14 mm 2 , possibly due to issues of resolution, machine settings and individual examination technique, but most of the articles set the cut-off value of CSA-I at 9-11 mm 2 (Tai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography is widely used to investigate compression of the median nerve in the carpal tunnel (FIG. 1), and these studies have provided standard criteria for the diagnosis of all nerve entrapments with ultrasonography 36,37 . One meta-analysis of papers that reported the sensitivity and specificity of ultra sonography from clinical or nerve conduction studies showed that ultrasonography has a sensitivity of 77.6% and a specificity of 86.8% for diagnosis of carpal tunnel syndrome (CTS) 38 .…”
Section: Entrapment Neuropathiesmentioning
confidence: 99%
“…Interestingly, abnormalities in ultrasonographic images have a linear correlation with hand function (for example, fine finger movement) -the larger the nerve cross-sectional area, the greater the impairment -but not with the severity of the symptoms (such as paraesthesias and dysaesthesias) 39 . Nevertheless, evidence-based guidelines state that the median nerve cross-sectional area at the wrist is of value in combination with nerve conduction studies, and can be used as a diagnostic test 36 . Intraneural Doppler sonography might have a role in the diagnosis of CTS, but what this role is remains unclear owing to technical limitations and a lack of standardization in depicting the vasa nervorum as a sign of inflammation 37 .…”
Section: Entrapment Neuropathiesmentioning
confidence: 99%
“…[14] For wrist, US has been used for diagnosis of anatomical anomalies like bifid median nerve and for therapeutic interventions. [15] US has been found quite useful in trochanteric pain during interventions in hip joint, in interventions related to knee joint and plantar fascia. [16] For interventions in knee joint, US has limited use due to limited visualization of cruciate ligament, meniscopathy and fractures.…”
Section: Musculoskeletal Interventions In Chronic Painmentioning
confidence: 99%